Potential for radical change in Higher Education learning spaces after the pandemic (Journal of Applied Learning and Teaching, 2020)
The article situates the challenges that higher education faces before the onset of COVID-19. A future that situates disruptive and immediate transformation for higher education curricula is described to save global universities from the ravages of the “stay-at-home” policies. The move to a totally online environment took place overnight, and most institutions of higher education were totally unprepared. Yet, a future of possibilities could be adopted in the coming five years, one, in particular, being game-based learning, an andragogy based upon experiential education.